Septal deviation and other factors increase the risk of barotitis media in high altitude high opening training (Medical Journal of Indonesia, 2008)
Barotitis media (BM) frequently occurr in High Altitude High Opening (HAHO) training simulation as a result from rapid change of pressure. The aim of this study was to investigate septal deviation and other risk factors that increase the risk of BM. This experimental study was conducted at the Indonesian Center for Aviation Medicine and Health (Lakespra Saryanto) during May – July 2007 involving Indonesian Armed Forces (TNI) HAHO training. Medical examinations were performed before and after training. An otolaryngologist confirm the diagnosis of BM. Cox regression analysis using STATA 9.0 program was performed to identify dominant risk factors for BM. A number of 177 subjects participated in this study. We found 56.5% had BM after training. Septal deviation was found in 28.8% of the subjects and it moderately increased the risk of BM by 23% than normal septum [adjusted relative risk (RRα) = 1.23; 95% confidence interval (CI) = 0.95 – 1.60; p=0.123]. Those who have been smoking for 1-3 years had 70% increase risk for BM than non-smoking subjects (RRα= 1.68; 95% CI = 1.17 – 2.42). Those who have been in the force for 5 years or longer were 50% more at risk for BM than those who have been in the force less than 5 years. In addition, trainees had 40% higher risk than subjects with special qualifications for HAHO (RRα = 1.40; 95% CI = 0.99 – 1.97; p = 0.051). Special caution need to be applied for those who had septal deviation, longer working period, habit of smoking for 1-3 years, and trainees to minimize the risk of BM. (Med J Indones 2008; 17: 37-42) Keywords: barotitis media, septal deviation, HAHO training simulation